PENERAPAN ROLE PLAYING UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR IPS KELAS V - Sulistyorini, Endah; Kristin, Firosalia (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2017)
Abstrack : The background of this research students' low motivation with an average of57.95 and learning outcomes of 13 students (65%) under the KKM (â‰¥65). The purpose of thisstudy to increase motivation and student learning outcomes using model role playing. Thistype of research is a classroom action research with two cycles beginning stages of planning,implementation, observation and reflection. Questionnaire to collect data motivation to learn,about the test, the observation sheet attitudes and skills for student learning outcomes. Datausing descriptive analysis techniques. Motivation in the first cycle